EFFECTIVENESS OF SOCIAL POLICY: THEORETICAL ASPECT AND METHODOLOGICAL PRINCIPLES OF ASSESSMENT - Urchik, Gаlina (Social Economics, 2020)
According to the results of generalization and critical study of existing scientific achievements, it is found that the vast majority of them are limited to the need to improve the effectiveness of social policy or identify general approaches to its evaluation based on living standards.  This led to the goal of this study, which is to specify the essence and development of methodological principles for evaluating the effectiveness of the national social policy.  According to the results of the research, the essence is specified and the structural and logical model of evaluation of social policy efficiency is determined.  It is substantiated that the primary in assessing the effectiveness of the social policy should be an objective approach, in which quantitative measures can be: 1) effectiveness (the ratio of the result to the resources used to achieve it); 2) the degree of achievement of goals (compliance of the result with certain goals).  The author’s position is that it is advisable to assess the effectiveness of the social policy in terms of its structural components according to the relevant system of indicators, the list of which is formed taking into account their ability to reflect the results of a particular structural component of the JV and information availability of relevant data. The novelty of this study is to substantiate the procedure for evaluating the effectiveness of the national social policy by the criterion of achieving the goals. They are determined at the level of maximum / minimum values of reference indicators, respectively, for stimulants / disincentives for the entire period of Ukraine’s Independence.  Approbation of the author’s methodology for evaluating the effectiveness of the national joint venture for 2014-2019 showed the unavailability of reference values (on average by 0.12-0.18).  Such structural components of the social policy as the policy of social protection, labor market, and distribution and redistribution of the social product have a relatively low level of efficiency in Ukraine. It indicates the priority vector of the Government’s activity.  The proposed and tested author’s method of evaluating the effectiveness of the social policy is not without drawbacks in terms of the formation of the resulting indicators and disregard for the importance of structural components (individual indicators) in ensuring the effectiveness of the social policy.  Nevertheless, it offers a specific approach to quantifying the effectiveness of the social policy, which can be improved and changed depending on changes in objectives, information availability, sufficient justification of the importance of the components of the social policy.